Palladium-catalyzed alkoxycarbonylation of aryl halides with phenols employing formic acid as the CO source. Issue 8 (14th December 2015) - Qi, Xinxin; Li, Chong-Liang; Jiang, Li-Bing; Zhang, Wan-Quan; Wu, Xiao-Feng
Abstract : An efficient palladium-catalyzed alkoxycarbonylation of aryl halides with phenols has been developed. Various aryl benzoates have been isolated in good to excellent yields with formic acid as the CO source. Abstract : An efficient palladium-catalyzed alkoxycarbonylation of aryl halides with phenols has been developed. Various aryl benzoates have been isolated in good to excellent yields with formic acid as the CO source. The reaction proceeds smoothly under mild conditions and good functional group tolerance was observed.